Gastronomía en la provincia de Cotopaxi. - Mocha Aules, Gabriela Estefanía (2023)
This present investigative project corresponds to a gastronomic study of province Cotopaxi, due to lack of information on gastronomy province, it was identified that inhabitants eat fast food (hot dogs, salchipapas, shawarmas), with great acceptance by this was raised to make a gastronomic guide of each canton. A first objective, the qualitative approach for documentary research was obtained through inductive method, which was obtained to carry out situational diagnosis of the province, using as a classification technique from obtained information, with the help of the instruments; PDOT (Development and Territorial Planning Plan), thesis and bibliographic review where a diagnosis of four areas was made; sociocultural, economic, environmental, tourist resulting on area situational diagnosis. Going on with objective 2, the application of field research was carried out through ethnographic method that helps to obtain updated information, which allowed to collect information to be applied by open interview technique, audiovisual recording, direct observation with INPC instrument (Instituto National Cultural Heritage) and photographs, and thus a record of 38 gastronomic dishes in different cantons were obtained, the sheets cover all the necessary information and with this the gastronomy of the place is known, with relevant information that was needed to take inventory. Finishing with objective 3 through descriptive research together with synthetic method, a documentary analysis was carried out as a technique for the realization of the structure and design of the gastronomic guide using instruments such as CANVA Software and the photographs, which makes the description known. of inventoried dishes, as well as their location and origin place described by each place. This will allow to disseminate types of gastronomic dishes that exist for inhabitants knowledge. For national and foreign tourists.